Pedagogical Potential of the Folk Calendar in the Educational Process of Primary School - E. Kashekova, Irina; ., .; ., . (International Journal of Engineering and Technology, 2018)
The article reveals the possibilities of improving the quality of education in the context of an interdisciplinary integrated approach to learning based on immersion in traditional culture and mastering a universal complex of folk calendar, which possesses a striking pedagogical potential in the formation of a holistic view of the world, the development of strategic and associative thinking, and instilling of environmental culture of the individual. The pedagogical potential of the folk calendar is an optimal complex that integrates into education various fields of knowledge, such as natural cycles and phenomena, geographical features of the area and the encompassing landscape, local historical collisions, customs and folklore, folk beliefs and fairy tales, and the specifics of folk ornaments decorating household items and tools of trade. The study of the folk calendar complex in primary or basic school makes it possible providing a holistic presentation of learning material scattered in different subjects. Integrating the content of subjects studying the world around us, such as mathematics, literary reading, the Russian language, visual arts, music, and technology will help the child to understand not only the diversity and richness of the world, but also the existing interconnections. At the same time, games, proverbs, sayings, bright and expressive folklore images, images of mythological characters will cause interest of the child, and thus help him to master new information on various subjects at the emotionally positive background. Â